NARRATIVE REVIEW: ARECA NUT AS A HEALTHY AND HALAL PRODUCT FROM SCIENCE PERSPECTIVE IN PREVENTION OF NONCOMMUNICABLE DISEASES - Rd. Halim; Yuliawati Yuliawati; Muhammad Faizal Fathurrohim; Fitriyani Fitriyani; Siska Dwi Anggraeni; Kiki Safitri (Universitas Mathla’ul Anwar Banten, 2021)
One of efforts to improve public health is to utilize medicinal plants obtained from nature, which are economical and do not have side effects. Type of medicinal plants that is often used by people in Indonesia is Areca Nut. Empirically areca nut are able to overcome various types of diseases. The purpose of this review was to provide confidences in the feasibility of areca nut as raw material for medicinal plants and processed products. The results of the study showed that the potential of areca nut as antibacterial, anti-oxidant and control prevention of noncommunicable diseases. The direct use of areca nut is only as an ingredient with betel leaves and only certain people are able to consume it, while the benefits and efficacies are very diverse, innovation is needed to utilize areca nut in the processing of various healthy and halal food products in the form of flour, candy and coffee. Research is needed to determine the right formulation for physical, chemical and organoleptic efficacies, so that a product that is both healthy and halal can be obtained.